IMPLEMENTASI INQUIRY SOCIAL COMPLEXITY UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA DALAM PELAJARAN PPKn - Venny Rika; Dewa Bagus Sanjaya; I Gusti Ketut Arya Sunu (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
This research aims to improve critical thinking skills and student learning outcomes with the Inquiry Social Complexity model in class X MIPA 2 SMAN 4 Singaraja in PPKn lessons. Collecting data using the method of observation, tests and documentation. The results showed that there had been an increase in critical thinking skills and student learning outcomes for 2 cycles. In the first cycle of the second meeting, a percentage of 65% was obtained from the initial conditions, namely 40% of 40 students. Researchers have a minimum target of 70% of students have critical thinking skills. The second cycle of the 2nd meeting succeeded in obtaining a percentage of 87.5% or as many as 35 students actively criticized the lesson. Student learning outcomes have also increased, with the initial condition being an average score of 73,875 or only 55% of students who have achieved KKM 75 to an average of 79,125 or 70% in cycle I. Researchers have a target of at least 80% of students having achieved KKM 75 out of 40 student. Cycle II succeeded in achieving the target of obtaining an average score of 84.125 or a percentage of 90% of 40 students. The success of the implementation of the inquiry social complexity learning model is seen by the change in the attitude of students who are enthusiastic in learning to find and solve their own problems. The main obstacle faced by researchers is convincing students to be confident and dare to learn new things.